World citizenship : cosmopolitan thinking and its opponents - Heater, Derek Benjamin (Continuum studies in citizenship., 2004)
Recent years have seen the development of a substantial literature on cosmopolitan political thought and the idea of world citizenship. In this book Derek Heater offers a concise and accessible survey of this complex debate. He aims both to interpret these concepts and to assist in their comprehension. Central to the organization of the book is Heater's claim that the notion of world citizenship remains weak unless it is able to stand alongside and be comparable to citizenship in its traditional state-embedded sense. Thus, the core chapters are arranged according to a basic breakdown of the ke.